On stage : theater games and activities for kids - Bany-Winters, Lisa. (Chicago, Ill. : Chicago Review Press, 1997)
Covers basic theater vocabulary, puppetry and pantomime, sound effects, costumes, props, and makeup; includes several play scripts.
Includes bibliographical references.
Booklist.
School Library Journal.
6.6
3-6
Keywords: Children's plays, American; Drama in education; Play; Drama in education; Plays; Children's plays; Drama in education